Optimalisasi Potensi Pemuda dalam Komunitas Perdamaian di Kota Malang dengan Implementasi Kelas Literasi Kewarganegaraan dan Pengembangan Media Digital yang Menjunjung Tinggi Nilai-Nilai Inklusif - Alfaqi, Mifdal Zusron; Aris Shofa, Abd. Mu’id; Wafa, Alfian Fawaidil; Fattah, Zulfikar Waliyuddin; Maisaroh, Anisa Amalia; Agung, Laksamana Prammana (Islamic Insights Journal, 2024)
Malang City is one of the cities in Indonesia with high cultural and religious diversity. However, this diversity also has the potential to lead to social conflicts. This community service program aims to optimize the potential of youth in peace communities in Malang City by implementing civic literacy classes and developing digital media that upholds inclusive values. This program is carried out in several stages, namely (1) identification and selection of participants from youth groups, (2) conducting civic literacy classes that include material on citizens' rights and obligations, tolerance, and diversity, (3) training in digital media development to spread messages of peace and inclusiveness, and (4) monitoring and evaluation to assess program effectiveness. The program succeeded in increasing young people's understanding and awareness of the importance of civic literacy and inclusive values. Participants also demonstrated better abilities in utilizing digital media for peace and inclusivity campaigns. As a result, there was an increase in youth participation in positive and collaborative community activities.